Molecular Basis for the Biosynthesis of the Siderophore Coprogen in the Cheese-Ripening Fungus Penicillium Roqueforti - Chavez-Rosales, R; Gil-Duran, C (BioMed Central Ltd, 2025)
Background: Iron is an essential nutrient for microorganisms, including fungi, which have evolved strategies to acquire it. The most common strategy is the secretion of siderophores, low-molecular-weight compounds with a high affinity for ferric ions, which are involved in cellular iron uptake. Penicillium roqueforti, the fungus responsible for the ripening of blue-veined cheeses, produces coprogen, a hydroxamate-type siderophore. However, to date, the molecular basis for its biosynthesis remains elusive. Results: In this study, we identified and characterized a biosynthetic gene cluster (BGC) responsible for coprogen biosynthesis in P. roqueforti, named the cop BGC. This BGC contains seven genes, three of which (copA, copB and copE) encode enzymes directly involved in coprogen biosynthesis from precursors molecules. Using CRISPR-Cas9, we targeted these three genes and analyzed the resulting mutants by Liquid Chromatography/High-Resolution Mass Spectrometry (LC/HRMS). Our results confirmed that all three genes are necessary for coprogen biosynthesis. Phenotypically, the mutants displayed growth differences under iron-deficient conditions, which correlated with their ability to either synthesize or fail to synthesize coprogen B and dimerumic acid, intermediates in the coprogen pathway with siderophore activity. Conclusions: The results obtained in this work provide important insights into the molecular basis of coprogen biosynthesis in P. roqueforti, enhancing the understanding of how siderophores enable this fungus to thrive in iron-deficient environments. © The Author(s) 2025.